Different Patterns and Distribution of Skull Fractures in Road Traffic Accidents (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The head is a common site of trauma in road accidents, and despite safety initiatives, the mortality rate for head injuries has not decreased. Despite the existence of a mandatory helmet law, both mortality and morbidity rates are on the rise. Head injuries are also associated with injuries to the neck, spine, stomach, abdomen, and pelvic cavity.Objectives: To study different patterns and distribution of skull fractures in different kinds of road accidents.Methods: In the Department of Forensic Medicine at Osmania General Hospital 4,213 post-mortem Examinations were carried out during the period ( August 2019 to January 2021. In 784 cases, death was attributed to Road Traffic Accidents. Head injury was present in 634 cases. In 471 cases out of 784, skull fractures were found. The data has been collected from PME reports and inquest reports, relatives and friends of the deceasedResults: Most frequently noted type of fracture is fissured in 59.8% of the cases. Injuries in RTA’s are almost always due to blunt force on cranial vault. Highest number of fractures are seen in temporal 100 (21%), Fractures occurring in cranial vault alone is 336(71.3%), BOS alone is 28(5.94%). Fractures extending into BOS are 308(65.3%). In the base of skull, overall highest frequency of fracture is found in MCF (alone in BOS) with 109 (23.1%), then in PCF (alone in BOS) is 71 (15%), least in ACF 39(8.28%). Only fracture MCF in all over skull is seen in 11(2.33%) cases, PCF 11(2.33%) casesConclusion: Commonest fracture of skull in road traffic accidents is the fissured fracture in the cranial vault, mostly in temporal bone. Fractures of cranial vault most frequently extend to middle cranial fossa and posterior cranial fossa till foramen magnum which are responsible for immediate deaths. Victims who survived till hospital admission are almost half in number. Strict enforcement of road safety regulations and improving emergency medical services may prevent untimely deaths and disabilities caused by RTAs.
Keywords: Road Traffic Accidents, RTA, Base of Skull, BOS, MCF, ACF, PCF